Sosialisasi Aplikasi Monitoring Brazilian Jiu Jitsu Sebagai Sarana Pelatihan Beladiri di Universitas Mercu Buana - Bagus Priambodo; Yuwan Jumaryadi; Radityo Muhamad (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
Brazilian Jiu Jitsu martial arts training usually consists of training techniques followed by repetition. In the Brazilian Jiu Jitsu class the instructor will correct, calibrate, and correct mistakes, whether big or small mistakes made by Brazilian Jiu Jitsu students when performing techniques. When the details of a technique have been studied, then this technique will be repeated in a situation when it is necessary to use it. At this time students cannot remember exactly how many times they have repeated a technique. This makes it difficult for instructors to monitor the progress of Brazilian Jiu Jitsu students. In this community service, Brazilian Jiu Jitsu instructors and students will be provided with a Brazilian Jiu Jitsu mobile application. In addition, training was also given and accompanied to use mobile applications in Brazilian Jiu Jitsu classes.